ANALYSIS RELATES TO THE IMPACT FROM MACROECONOMIC FACTORS TO BANKING STOCK RETURNS WHICH MEDIATED BY PROFITABILITY - Hedwigis Esti Riwayati; Muhammad Affid Diena (Dinasti International Journal of Education Management And Social Science, 2021)
This research aims to analyze the impact which caused by macroeconomic factors to stock returns which mediated by profitability. This research used purposive sampling method with BUKU IV Banks who Listed on the Indonesia Stock Exchange as sample in this research period. The data was taken from the quarterly financial reports of the sample banks and Bank Indonesia. The analysis technique that used in this research are panel data regression and used path analysis to reveal the impact which caused by intervening variable. The results found that interest rates had no significant impact towards stock returns, while the inflation rate and the rupiah exchange rate had a direct significant impact on stock returns. Path analysis found that interest rates, inflation rates and Rupiah exchange rate had no significant affect on stock returns which indirectly mediated by profitability. This research results are very useful as an information for investors and stakeholders to determine good investment decisions in the banking sector.